Development of a Scale Measuring Chinese Preservice Physical Education Teachers’ Beliefs About the Physical Education Profession - Fan, Yao; Keating, Xiaofen D.; Liu, Jingwen; Zhou, Ke; Shangguan, Rulan; Knipe, Robert (The Asia-Pacific Education Researcher, 2018)
This project aimed to develop a valid and reliable scale measuring Chinese preservice physical education teachers’ beliefs about the physical education profession (PPET-BPEP). The domains and items were created from a conceptual analysis of the previous literature and PPETs’ responses to an open-ended survey. Six experts in the field of physical education and educational psychology evaluated the content validity of the scale. The reliability and factorial validity of the scale were examined utilizing a sample of 696 Chinese PPETs. The PPET-BPEP scale with 12 items embedded in two domains revealed acceptable content validity, internal structure validity, and internal consistency. The two domains were labeled as “sense of calling” and “value of physical education profession” based on the shared content of items in each domain. We recommend using PPET-BPEP scale for PPET recruitment and preparation. The scale can also help establish teacher belief scales in other subject matters. Future validation of the scale is needed in different countries and institutions.
Keywords: Future physical education teacher; Professional beliefs; Survey development; Validity and reliability; dept.hms

Association of accelerometry-measured physical activity and cardiovascular events in mobility-limited older adults: The LIFE (Lifestyle Interventions and Independence for Elders) study - Cochrane, S.K.; Chen, S.-H.; Fitzgerald, J.D.; Dodson, J.A.; Fielding, R.A.; King, A.C.; McDermott, M.M.; Manini, T.M.; Marsh, A.P.; Newman, A.B.; Pahor, M.; Tudor-Locke, C.; et al. (Journal of the American Heart Association, 2017)
Background--Data are sparse regarding the value of physical activity (PA) surveillance among older adults-particularly among those with mobility limitations. The objective of this study was to examine longitudinal associations between objectively measured daily PA and the incidence of cardiovascular events among older adults in the LIFE (Lifestyle Interventions and Independence for Elders) study. Methods and Results--Cardiovascular events were adjudicated based on medical records review, and cardiovascular risk factors were controlled for in the analysis. Home-based activity data were collected by hip-worn accelerometers at baseline and at 6, 12, and 24 months postrandomization to either a physical activity or health education intervention. LIFE study participants (n=1590; age 78.9±5.2 [SD] years; 67.2% women) at baseline had an 11% lower incidence of experiencing a subsequent cardiovascular event per 500 steps taken per day based on activity data (hazard ratio, 0.89; 95% confidence interval, 0.84-0.96; P=0.001). At baseline, every 30 minutes spent performing activities ≥500 counts per minute (hazard ratio, 0.75; confidence interval, 0.65-0.89 [P=0.001]) were also associated with a lower incidence of cardiovascular events. Throughout follow-up (6, 12, and 24 months), both the number of steps per day (per 500 steps; hazard ratio, 0.90, confidence interval, 0.85-0.96 [P=0.001]) and duration of activity ≥500 counts per minute (per 30 minutes; hazard ratio, 0.76; confidence interval, 0.63-0.90 [P=0.002]) were significantly associated with lower cardiovascular event rates. Conclusions--Objective measurements of physical activity via accelerometry were associated with cardiovascular events among older adults with limited mobility (summary score > 10 on the Short Physical Performance Battery) both using baseline and longitudinal data. © 2017 The Authors.
Keywords: Accelerometry; Actigraphy; Age Factors; Aged; Aged, 80 and over; Aging; Article; Cardiovascular; Cardiovascular Diseases; Exercise; Exercise Therapy; Female; Fitness Trackers; Geriatric Assessment; Health Knowledge, Attitudes, Practice; Humans; Incidence; Male; Mobility Limitation; Patient Education as Topic; Physical activity; Predictive Value of Tests; Prognosis; Protective Factors; Risk Factors; Risk Reduction Behavior; Time Factors; United States; accelerometry; actimetry; activity tracker; age; aged; aging; attitude to health; cardiovascular disease; cardiovascular risk; clinical study; clinical trial; confidence interval; controlled study; dept.hms; devices; exercise; female; follow up; geriatric assessment; hazard ratio; health education; human; incidence; kinesiotherapy; lifestyle; major clinical study; male; medical record review; morbidity; multicenter study; patient education; phase 3 clinical trial; physical activity; physical mobility; predictive value; priority journal; prognosis; protection; randomized controlled trial; risk factor; risk reduction; time factor; very elderly; walking difficulty

Associations Between Ankle-Brachial Index and Cognitive Function: Results From the Lifestyle Interventions and Independence for Elders Trial - Espeland, M.A.; Newman, A.B.; Sink, K.; Gill, T.M.; King, A.C.; Miller, M.E.; Guralnik, J.; Katula, J.; Church, T.; Manini, T.; Reid, K.F.; McDermott, M.M.; et al. (Journal of the American Medical Directors Association, 2015)
Objective: The objective of this study was to evaluate cross-sectional and longitudinal associations between ankle-brachial index (ABI) and indicators of cognitive function. Design: Randomized clinical trial (Lifestyle Interventions and Independence for Elders Trial). Setting: Eight US academic centers. Participants: A total of 1601 adults ages 70-89 years, sedentary, without dementia, and with functional limitations. Measurements: Baseline ABI and interviewer- and computer-administered cognitive function assessments were obtained. These assessments were used to compare a physical activity intervention with a health education control. Cognitive function was reassessed 24 months later (interviewer-administered) and 18 or 30 months later (computer-administered) and central adjudication was used to classify individuals as having mild cognitive impairment, probable dementia, or neither. Results: Lower ABI had a modest independent association with poorer cognitive functioning at baseline (partial r= 0.09; P < .001). Although lower baseline ABI was not associated with overall changes in cognitive function test scores, it was associated with higher odds for 2-year progression to a composite of either mild cognitive impairment or probable dementia (odds ratio 2.60 per unit lower ABI; 95% confidence interval 1.06-6.37). Across 2 years, changes in ABI were not associated with changes in cognitive function. Conclusion: In an older cohort sedentary individuals with dementia and with functional limitations, lower baseline ABI was independently correlated with cognitive function and associated with greater 2-year risk for progression to mild cognitive impairment or probable dementia. © 2015 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Aged; Aged, 80 and over; Ankle Brachial Index; Ankle-brachial index; Article; Cognition; Cognitive function; Cross-Sectional Studies; Dementia; Disability Evaluation; Exercise; Female; Geriatric Assessment; Health Education; Humans; Male; Mini Mental State Examination; Peripheral artery disease; Sedentary Lifestyle; United States; aged; ankle brachial index; clinical trial; cognition; controlled study; cross-sectional study; dementia; dept.hms; disability; episodic memory; executive function; exercise; female; follow up; geriatric assessment; health education; human; human experiment; learning; longitudinal study; male; mild cognitive impairment; multicenter study; normal human; physical activity; physical performance; randomized controlled trial; recall; sedentary lifestyle; spatial orientation; very elderly; working memory

Effect of hospitalizations on physical activity patterns in mobility-limited older adults - Wanigatunga, Amal A.; Gill, Thomas M.; Marsh, Anthony P.; Hsu, Fang-Chi; Yaghjyan, Lusine; Woods, Adam J.; Glynn, Nancy W.; King, Abby C.; Newton, Jr., Robert L.; Fielding, Roger A.; Pahor, Marco; Manini, Todd M.; et al. (Journal of the American Geriatrics Society, 2019)
OBJECTIVES: To evaluate the effect of hospitalizations on patterns of sedentary and physical activity time in mobility-limited older adults randomized to structured physical activity or health education. DESIGN: Secondary analysis of investigator-blinded, parallel-group, randomized trial conducted at 8 U.S. centers between February 2010 and December 2013. PARTICIPANTS: Sedentary men and women aged 70 to 89 at baseline who wore a hip-fitted accelerometer 7 consecutive days at baseline and 6, 12, and 24 months after randomization (N=1,341). MEASUREMENTS: Participants were randomized to a physical activity (PA; n = 669) intervention that included aerobic, resistance, and flexibility training or to a health education (HE; n = 672) intervention that consisted of workshops on older adult health and light upper-extremity stretching. Accelerometer patterns were characterized as bouts of sedentary (¡100 counts/min; ¿= 1, ¿= 10, ¿= 30, ¿= 60 minute lengths) and activity (¿= 100 counts/min; ¿= 1, ¿= 2, ¿= 5, ¿= 10 minute lengths) time. Each participant was categorized as having 0, 1 to 3, or 4 or more cumulative hospital days before each accelerometer assessment. RESULTS: Hospitalization increased sedentary time similarly in both intervention groups (8 min/d for 1-3 cumulative hospital days and 16 min/d for ¿= 4 cumulative hospital days). Hospitalization was also associated with less physical activity time across all bouts of less than 10 minutes (¿= 1: -7 min/d for 1-3 cumulative hospital days, -16 min/d for ¿= 4 cumulative hospital days; ¿= 2: -5 min/d for 1-3 cumulative hospital days, -11 min/d for ¿= 4 cumulative hospital days; ¿= 5: -3 min/d for 1-3 cumulative hospital days, -4 min/d for ¿= 4 cumulative hospital days). There was no evidence of recovery to prehospitalization levels (time effect p ¿ .41). PA participants had less sedentary time in bouts of less than 30 minutes than HE participants (-8 to -10 min/d) and more total activity (+3 to +6 min/d), although hospital-related changes were similar between the intervention groups (interaction effect p ¿ .26). CONCLUSION: Participating in a PA intervention before hospitalization had expected benefits, but participants remained susceptible to hospitalization's detrimental effects on their daily activity levels. There was no evidence of better activity recovery after hospitalization.
Keywords: accelerometer; clinical trial; dept.hms; exercise; hospital; peer-reviewed; sedentary behavior